Prosperity gospel in Kenyan urban centres: Come, see, pay and receive your miracles and healing - Ongong'a, Jude J.; Akaranga, Stephen I. (Research on Humanities and Social Sciences, 2015)
In this part of the 21st century, the impact of ‘New Age" religions created by secularization have exposed the western Christianity to several challenges which seem not only divergent to biblical doctrine but tend to give new image to God. Even here in Kenya, we are not foreign to these challenges. Some of which include; ordination of women, gender mainstreaming, marriage of the same sex, sex scandals of celibate clergy, leadership struggle, corruption and prosperity gospel, to mention but a few. This paper investigates the impact of prosperity gospel, an offshoot of neo-Pentecostalism in Kenyan urban centres with emphasis in Nairobi. This Christian social phenomenon teaches that true Christian faith results in material wealth and physical well-being. It claims that the Bible teaches that financial blessing is the will of God for Christians (vide Wikipedia, the free Encylopedia). That is, instead of the gospel of the forgiveness of sins, the centre is occupied by miracles and the improvement of the quality of life, along with temporal blessings from God (Anssi Simojoki, 2002: 272). This explains why the churches associated with prosperity gospel are popular in the eastern side of the city of Nairobi. The main question is whether the prosperity gospel is authentic Christian theology that satisfactorily improves the lives of the faithful? To facilitate our discussion, we have discussed the following four objectives: the origin and background of prosperity gospel, its teachings and impact, to make possible recommendations. The collection of data included both primary and secondary materials. We administered 250 oral interviews. Ninety members from the churches associated with the phenomenon, seventy students from both Kenyatta University and University of Nairobi and ninety adults outside the two categories.
free